The key role of microRNA-766 in the cancer development - Gupta, Jitendra; Kareem Al-Hetty, Hussein Riyadh Abdul; Aswood, Murtadha Sh.; Turki Jalil, Abduladheem; Azeez, Maha Dhurgham; Aminov, Zafar; Alsaikhan, Fahad; Ramírez-Coronel, Andrés Alexis; Ramaiah, Pushpamala; Farhood, Bagher (Frontiers in Oncology, 2023)
Cancer is caused by defects in coding and non-coding RNAs. In addition, duplicated biological pathways diminish the efficacy of mono target cancer drugs. MicroRNAs (miRNAs) are short, endogenous, non-coding RNAs that regulate many target genes and play a crucial role in physiological processes such as cell division, differentiation, cell cycle, proliferation, and apoptosis, which are frequently disrupted in diseases such as cancer. MiR-766, one of the most adaptable and highly conserved microRNAs, is notably overexpressed in several diseases, including malignant tumors. Variations in miR-766 expression are linked to various pathological and physiological processes. Additionally, miR-766 promotes therapeutic resistance pathways in various types of tumors. Here, we present and discuss evidence implicating miR-766 in the development of cancer and treatment resistance. In addition, we discuss the potential applications of miR-766 as a therapeutic cancer target, diagnostic biomarker, and prognostic indicator. This may shed light on the development of novel therapeutic strategies for cancer therapy.